Resilience as a Political Ideal. Issue 1 (2nd January 2016) - Kolers, Avery
Abstract: "Resilience" is booming. No longer a mere metaphor or abstract reference to dispositional properties, the resilience of communities or social-ecological systems is increasingly grounded in specific first-order properties. Consequently, resilience now constitutes a contentful and achievable partial conception of a good society. Yet political philosophers have taken little notice. The current article first discerns within recent social-scientific literature a set of attainable and measurable first-order properties that constitute "community resilience" or "ecological resilience." Then, specifying "resilience" as the resilience of high-HDI democratic societies to environmental disasters, infrastructure failures, and economic collapse, the current article argues from within a liberal framework that both "classical" (Lockean) and "egalitarian" (Rawlsian) liberals must treat resilience so understood as a necessary condition of legitimacy and justice; and this conclusion forces an overhaul of these liberal theories. Taking community resilience seriously requires both methodological and substantive revisions of the liberal enterprise.